Efficacy of two novel 2,2’-bifurans to inhibit methicillin-resistant Staphylococcus aureus infection in male mice in comparison to vancomycin - El-Sayed WM; Hussin WA; Ismail MA (Dove Medical Press, 2012)
Wael M El-Sayed,1,2 Warda A Hussin,3 Mohamed A Ismail1,41Departments of Biological Sciences and Chemistry, King Faisal University, Al-Hofuf, Saudi Arabia; 2Department of Zoology, University of Ain Shams, Cairo, Egypt; 3Department of Botany and Microbiology, Al-Azhr University, Cairo, Egypt; 4Department of Chemistry, Mansoura University, Mansoura, EgyptAbstract: The therapeutic efficacy of two novel bifurans and vancomycin in an animal model of a methicillin-resistant Staphylococcus aureus (MRSA) infection was compared. Adult male CF-1 mice (25–35 g) were intraperitoneally injected with 200 µL/mouse containing 107 cell-forming units of MRSA. After 16 hours, animals were treated with 110 mg/kg of vancomycin, or 5 mg/kg of mononitrile bifuran (1A) or monocationic bifuran (1B) and killed after 8 hours. Treatment with bifurans did not cause any toxicity. Treatment of MRSA-infected animals with bifurans resulted in significant reductions in the viable bacterial count in blood, liver, kidney, and spleen. Colonies recovered from livers and kidneys of mice injected with 1A or 1B lost the initial resistance pattern and became susceptible to methicillin and ciprofloxacin. MRSA elevated the serum urea level and activities of alanine aminotransferase and γ-glutamyl transpeptidase. MRSA also elevated the hepatic level of malondialdehyde, and serum levels of tumor necrosis factor and interleukin-6. MRSA also reduced the glutathione content and activities of catalase and glutathione S-transferase in liver. Similar to vancomycin, bifurans ameliorated most of the previous effects. Compound 1B was superior to 1A, and sometimes both provided better antistaphylococcal agents than vancomycin against MRSA pathogenesis. The present findings along with our previous studies support further evaluation of the efficacy of these bifurans in clinical studies.Keywords: MRSA, bifuran derivatives, septicemia, glutathione system, antioxidants